Urotensin‐II receptor is over‐expressed in colon cancer cell lines and in colon carcinoma in humans. (22nd January 2014) - Federico, Alessandro; Zappavigna, Silvia; Romano, Marco; Grieco, Paolo; Luce, Amalia; Marra, Monica; Gravina, Antonietta Gerarda; Stiuso, Paola; D'Armiento, Francesco Paolo; Vitale, Giovanni; Tuccillo, Concetta; Novellino, Ettore; et al.
Abstract Background Urotensin (U)‐II receptor (UTR) has been previously reported to be over‐expressed in a number of tumours. Whether UTR‐related pathway plays a role in colon carcinogenesis is unknown. Methods We evaluated UTR protein and mRNA expression in human epithelial colon cancer cell lines and in normal colon tissue, adenomatous polyps and colon cancer. U‐II protein expression was assessed in cancer cell lines. Moreover, we evaluated the effects of U‐II(4‐11) (an UTR agonist), antagonists and knockdown of UTR protein expression through a specific shRNA, on proliferation, invasion and motility of human colon cancer cells. Results Cancer cell lines expressed U‐II protein and UTR protein and mRNA. By immunohistochemistry, UTR was expressed in 5–30% of epithelial cells in 45 normal controls, in 30–48% in 21 adenomatous polyps and in 65–90% in 48 colon adenocarcinomas. UTR mRNA expression was increased by threefold in adenomatous polyps and eightfold in colon cancer, compared with normal colon. U‐II(4‐11) induced a 20–40% increase in cell growth while the blockade of the receptor with specific antagonists caused growth inhibition of 20–40%. Moreover, the knock down of UTR with a shRNA or the inhibition of UTR with the antagonist urantide induced an approximately 50% inhibition of both motility and invasion. Conclusions UTR appears to be involved in the regulation of colon cancer cell invasion and motility. These data suggest that UTR‐related pathway may play a role in colon carcinogenesis and that UTR may function as a target for therapeutic intervention in colon cancer.